2019
DOI: 10.1186/s40851-019-0123-5
|View full text |Cite
|
Sign up to set email alerts
|

Diminution of pharyngeal segmentation and the evolution of the amniotes

Abstract: BackgroundThe pharyngeal arches are a series of bulges found on the lateral surface of the head of vertebrate embryos, and it is within these segments that components of the later anatomy are laid down. In most vertebrates, the post-otic pharyngeal arches will form the branchial apparatus, while in amniotes these segments are believed to generate the larynx. It has been unclear how the development of these segments has been altered with the emergence of the amniotes.ResultsIn this study, we examined the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…S8A) (McCauley and Bronner-Fraser, 2006;Abrial et al, 2017;Adachi et al, 2018). Our finding that arch 6 develops differently to anterior arches is consistent with a recent study by Poopalasundaram et al (2019) showing that posterior PA development in amniotes is markedly distinct from that in other vertebrate clades. However, although Poopalasundaram et al suggest that myogenesis is suppressed in posterior PAs, we observed MYOD protein accumulation in posterior CPM in the anlagen of branchiomeric muscles derived from arches 4-6 from early developmental stages.…”
Section: Cpm and Ncc Rearrangement During Evolution Of The Vertebratesupporting
confidence: 92%
“…S8A) (McCauley and Bronner-Fraser, 2006;Abrial et al, 2017;Adachi et al, 2018). Our finding that arch 6 develops differently to anterior arches is consistent with a recent study by Poopalasundaram et al (2019) showing that posterior PA development in amniotes is markedly distinct from that in other vertebrate clades. However, although Poopalasundaram et al suggest that myogenesis is suppressed in posterior PAs, we observed MYOD protein accumulation in posterior CPM in the anlagen of branchiomeric muscles derived from arches 4-6 from early developmental stages.…”
Section: Cpm and Ncc Rearrangement During Evolution Of The Vertebratesupporting
confidence: 92%
“…Thus, there are three features that are associated with the pharyngeal pouches: 1they form during the segmental phase of pharyngeal development; 2they contact the overlying ectoderm; 3they express definitive molecular markers such as PAX1/9, TBX1, etc. (Poopalasundaram et al 2019). We can conclude that in amniotes, including humans, there are five arches and four pouches, and their relationship is as follows: pouch 1 lies between arches 1 and 2; pouch 2 between arches 2 and 3; pouch 3 between arches 3 and 4; and pouch 4 between arches 4 and the terminal arch.…”
Section: The Presence Of a Transient '5th' Pouch/arch?mentioning
confidence: 86%
“…; Poopalasundaram et al. ). There have, of course, been fewer studies of pharyngeal pouch formation in human embryos, but again morphology and analysis of PAX9 expression demonstrate the formation of four pouches (Farley et al.…”
Section: The Presence Of a Transient ‘5th’ Pouch/arch?mentioning
confidence: 99%
See 2 more Smart Citations